Sex-Dependent Shared and Nonshared Genetic Architecture Across Mood and Psychotic Disorders - Blokland, Gabriëlla A M; Grove, Jakob; Chen, Chia-Yen; Cotsapas, Chris; Tobet, Stuart; Handa, Robert; Schizophrenia Working Group of the Psychiatric Genomics Consortium; St Clair, David; Lencz, Todd; Mowry, Bryan J; Periyasamy, Sathish; Cairns, Murray J; et al. (Biological psychiatry, 2022)
BACKGROUND: Sex differences in incidence and/or presentation of schizophrenia (SCZ), major depressive disorder (MDD), and bipolar disorder (BIP) are pervasive. Previous evidence for shared genetic risk and sex differences in brain abnormalities across disorders suggest possible shared sex-dependent genetic risk. METHODS: We conducted the largest to date genome-wide genotype-by-sex (G×S) interaction of risk for these disorders using 85,735 cases (33,403 SCZ, 19,924 BIP, and 32,408 MDD) and 109,946 controls from the PGC (Psychiatric Genomics Consortium) and iPSYCH. RESULTS: Across disorders, genome-wide significant single nucleotide polymorphism-by-sex interaction was detected for a locus encompassing NKAIN2 (rs117780815, p = 3.2 × 10-8), which interacts with sodium/potassium-transporting ATPase (adenosine triphosphatase) enzymes, implicating neuronal excitability. Three additional loci showed evidence (p < 1 × 10-6) for cross-disorder G×S interaction (rs7302529, p = 1.6 × 10-7; rs73033497, p = 8.8 × 10-7; rs7914279, p = 6.4 × 10-7), implicating various functions. Gene-based analyses identified G×S interaction across disorders (p = 8.97 × 10-7) with transcriptional inhibitor SLTM. Most significant in SCZ was a MOCOS gene locus (rs11665282, p = 1.5 × 10-7), implicating vascular endothelial cells. Secondary analysis of the PGC-SCZ dataset detected an interaction (rs13265509, p = 1.1 × 10-7) in a locus containing IDO2, a kynurenine pathway enzyme with immunoregulatory functions implicated in SCZ, BIP, and MDD. Pathway enrichment analysis detected significant G×S interaction of genes regulating vascular endothelial growth factor receptor signaling in MDD (false discovery rate-corrected p < .05). CONCLUSIONS: In the largest genome-wide G×S analysis of mood and psychotic disorders to date, there was substantial genetic overlap between the sexes. However, significant sex-dependent effects were enriched for genes related to neuronal development and immune and vascular functions across and within SCZ, BIP, and MDD at the variant, gene, and pathway levels.
Keywords: Psychotic Disorders; Male; Genotype-by-sex interaction; Endothelial Cells; Genetic Predisposition to Disease; endoteliální buňky; Sex differences; Sex Characteristics; Receptors, Vascular Endothelial Growth Factor; Schizophrenia; Depressive Disorder, Major; Genome-Wide Association Study; Genome-wide association study; Major depressive disorder; mužské pohlaví; jednonukleotidový polymorfismus; receptory vaskulárního endoteliálního růstového faktoru; pohlavní dimorfismus; psychotické poruchy; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; Sulfurtransferases; Humans; sulfurtransferasy; schizofrenie; depresivní porucha unipolární; Bipolar disorder; Female; bipolární porucha; genetická predispozice k nemoci; celogenomová asociační studie; Bipolar Disorder